Refinements and innovations in biopsy and analysis techniques for pleural and lung disease - Diacon, Andreas Henri (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Medicine. Internal medicine))--University of Stellenbosch, 2007.